2008
DOI: 10.2337/dc08-s245
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Oxidative Stress in the Pathogenesis of Hypertension

Abstract: Recently oxidative stress has been proposed as the cause of hypertension. An imbalance in superoxide and nitric oxide production may account for reduced vasodilation, which in turn can favor the development of hypertension. In vitro and in human studies support this hypothesis. The supplementation of antioxidants, particularly in the form of fresh fruit and vegetables, reduces blood pressure, supporting a role for free radicals in hypertension.Diabetes Care 31 (Suppl. 2):S181-S184, 2008

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
136
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 55 publications
3
136
0
5
Order By: Relevance
“…The animals were placed in heated chamber at an ambient temperature of (30)(31)(32)(33)(34) 曟 ) for 15 min and from each animal, [1][2][3][4][5][6][7][8][9] blood pressure values were recorded. The lowest three readings were averaged to obtain a mean blood pressure.…”
Section: Measurement Of Blood Pressure By Non-invasive Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were placed in heated chamber at an ambient temperature of (30)(31)(32)(33)(34) 曟 ) for 15 min and from each animal, [1][2][3][4][5][6][7][8][9] blood pressure values were recorded. The lowest three readings were averaged to obtain a mean blood pressure.…”
Section: Measurement Of Blood Pressure By Non-invasive Methodsmentioning
confidence: 99%
“…CVD has reached epidemic proportions in India [2] and is estimated to result in more than 3 million deaths each year [3] . Hypertension is a major risk factor for cardiovascular diseases and a large body of evidence suggests oxidative stress, an increase in the production of reactive oxygen species (ROS), as a strong underlying factor in hypertension [4,5] . Excessive ROS generation has been suggested to be involved in a variety of cardiovascular diseases including hypertension, inflammation in the cardiovascular system, cardiac hypertrophy, cardiomyopathies and ischemic heart disease [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen free radicals have been reported to play an important role in the pathogenesis of a number of cardiovascular diseases (CVDs) such as atherosclerosis, ischemia, hypertension, cardiomyopathy, cardiac hypertrophy and congestive heart failure by both in vivo and in vitro studies [31][32][33][34][35]. Potential sources of free radicals during ischemia and reperfusion have been identified in myocytes, vascular endothelium, and leukocytes.…”
Section: Oxidative Stress and Cardiovascular Diseasesmentioning
confidence: 99%
“…There are numerous evidences suggesting that oxidative stress plays an important role in the development of hypertension [7][8][9] . It is possible that decreased antioxidant activity such as, superoxide dismutase and catalase and reduced levels of reactive oxygen species scavengers such as, vitamins E, C and glutathione contribute to oxidative stress 9 of which there are many crosssectional studies showing that vitamin C status is inversely associated with blood pressure.…”
mentioning
confidence: 99%
“…It is possible that decreased antioxidant activity such as, superoxide dismutase and catalase and reduced levels of reactive oxygen species scavengers such as, vitamins E, C and glutathione contribute to oxidative stress 9 of which there are many crosssectional studies showing that vitamin C status is inversely associated with blood pressure. Although some, but not all clinical trials have shown lowering effect of vitamin C on the level of blood pressure, scientific evidence especially in the Asian population is small 10 .…”
mentioning
confidence: 99%